Potensi Cidera Pada Olahraga Hapkido Provinsi Lampung - Yudistira, Efraldo; Khasanah, Al Um Aniswatun; Sefriana, Novi (Universitas Muhammadiyah Metro, 2022)
Injury conditions in martial arts based on epidemiological research are in the 10th position in dangerous sports with the potential for injury to reach 2.4% overall. The injury model that occurs each time is determined by a certain dominance technique of a discipline resulting from the philosophy of the sport discipline, training objectives, as well as from the rules of sports competition. The management of hapkido Lampung is aware of the lack of facilities for approaching medical science in injury management to review data and carry out training developments to minimize injuries.This study purpose was to determine the risk of injury to Hapkido Athletes in order to develop training programs to focus on preventing or reducing the potential for existing injuries so that athletes have maximum performance. This research is descriptive analytic research using cross sectional design . In this design a transverse approach is used. Where is the observation of the independent variable and the dependent variable is carried out only once at the same time with the number of research samples 60. The results of this study are data on the incidence of injuries experienced by hapkido athletes based on questionnaire data collection.The data obtained are 53.3% female samples and 46.7% male, with data on the incidence of injury 50.9% in the ankle region, and 44.4% specific tissue injury to joints and ligaments and the incidence of injury during technical training 50.9%. The incidence rate of injury to the hapkido martial arts athlete in Lampung has the largest presentation in the ankle region and in specific ligamentous tissues with the risk of it occurring during movement technique training activities where the results can be concluded that hapkido sports require good joint stability, especially in the ankle region.